STUDY OF THERMAL INTERACTION OF CELL-PHONE RADIATIONS WITHIN HUMAN HEAD TISSUES - BASANDRAI D; DHAMI AK (Asian Journal of Pharmaceutical and Clinical Research, 2016)
In the present investigation, a theoretical model based on Maxwell equations, microscopic form of ohm’s law and Joules law of heating effect is proposed for the study of penetration depth, attenuation coefficient and specific absorption rate (SAR) with varying distance between the source of radiation and exposed human head tissues (skin, fat, brain and bone). In addition, corresponding temperature increase inside these various human head tissues is also calculated. Results of present study indicate that the temperature rise in human tissue depends upon specific absorption rate and the duration for which human body is actually exposed to GSM radiations.Â By assuming the distance of 1cm and exposure time of 5 minutes, the highest SAR was estimated to be 1681.7 W/Kg for the brain tissue at 900 MHz and 4038.5 W/Kg for 1800 MHz. Maximum skin depth and attenuation coefficient was found to be in the case of fat and brain tissue, respectively amongst rest head tissues. The corresponding highest temperature rise for the brain tissue was calculated to be 2.31K at 900 MHz and 5.54K at 1800 MHz frequencies.